Pengaruh Kepuasan Kerja Pada Perilaku Kewargaan Organisasional Dengan Komitmen Organisasional Sebagai Variabel Pemediasi (Studi Kasus pada Bank Indonesia Kantor Cabang Semarang) - , SEKAR LARAS KINANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Job satisfaction is a vital factor in the management of human resources ( HR ) , because humans are the main assets that drive the company . When an employee has enough a job satisfaction , then they can carry out more functions outside their main job without any thought of reward . In relation to the quality of human resources as a factor in job satisfaction , organizational citizenship behavior ( OCB ) and organizational commitment will not be apart of the factors that affect the quality of a an individual performance . The cause that encourages employees to perform work outside of their job descriptions within an organization , in addition to job satisfaction is organizational commitment . The method used in this study is a quantitative method with a survey method to employees of Bank Indonesia Semarang Branch Office who have worked at least one year and take sample 60 employeeâs . The mediation test estimated using four regression equations according to the procedure of Baron and Kenny (1986 ) . The analytical method used is hierarchically with multiple analyzes using SPSS 19 for windows . The results of this study are job satisfaction has a positive effect on OCB and organizational commitment mediates the effect of job satisfaction on OCB partially.